2019
DOI: 10.3748/wjg.v25.i27.3563
|View full text |Cite
|
Sign up to set email alerts
|

Is the treatment outcome of hepatocellular carcinoma inferior in elderly patients?

Abstract: In view of the increasing life expectancy in different parts of the world, a larger proportion of elderly patients with hepatocellular carcinoma (HCC) requiring oncological treatment is expected. The clinicopathological characteristics of HCC in elderly patients and in younger patients are different. Elderly patients, in general, also have more comorbidities. Evaluation of the efficacy of different HCC treatment options in elderly patients is necessary to optimize treatment outcomes for them. Treatment modalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 82 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…The studies had a retrospective design with questionable validity, and the cut-off used for old age also varied, making direct comparison difficult. Nevertheless, the eligibility for LT should not be based only on age, but other factors must be considered in patients selection, such as the evaluation of liver function (through the model for end-stage liver disease—MELD), functional reserve (with the indocyanine green kinetics (ICG) test) and the assessment of liver stiffness (with transient elastography—LSM) [ 35 , 36 , 37 , 38 ]. In addition, recent studies showed that elderly HCC patients have different clinical and pathological characteristics compared to younger patients.…”
Section: Hcc Treatment In Elderly Patients According To Bclc Stagementioning
confidence: 99%
See 4 more Smart Citations
“…The studies had a retrospective design with questionable validity, and the cut-off used for old age also varied, making direct comparison difficult. Nevertheless, the eligibility for LT should not be based only on age, but other factors must be considered in patients selection, such as the evaluation of liver function (through the model for end-stage liver disease—MELD), functional reserve (with the indocyanine green kinetics (ICG) test) and the assessment of liver stiffness (with transient elastography—LSM) [ 35 , 36 , 37 , 38 ]. In addition, recent studies showed that elderly HCC patients have different clinical and pathological characteristics compared to younger patients.…”
Section: Hcc Treatment In Elderly Patients According To Bclc Stagementioning
confidence: 99%
“…The morbidity and mortality rates after hepatectomy in elderly HCC patients range from 9% to 51% and from 0% to 42.9%, respectively [ 46 ]. Due to recent advances in surgical procedures and perioperative management, most recent studies and meta-analyses have shown comparable short-term outcomes, such as hospital stay, post-operative morbidity and mortality, between younger and elderly patients undergoing hepatectomy for HCC [ 6 , 35 , 46 , 50 , 51 , 52 , 53 ]. This could probably be explained by the more careful selection criteria of elderly patients.…”
Section: Hcc Treatment In Elderly Patients According To Bclc Stagementioning
confidence: 99%
See 3 more Smart Citations